101 improv games for children and adults : fun and creativity with improvisation and acting - Bedore, Bob. (Alameda, CA : Hunter House, 2003)
101 Improv Games for Children and Adults starts with the basics of improvisational comedy, giving aspiring performers the building blocks required to think on their feet. A great resource for educators as well as for the professional actor or layperson, the book includes rules for 101 games that cover everything from easy warm-ups to over-the-top crowd pleasers, such as Fairy Tales, Bizarre Games, On Your Toes, and Narrative Games.
Introduction : The basics -- The games -- Antics for the advanced -- Putting on a show.
Keywords: Improvisation (Acting); Games